Improving on the network lifetime of clustered-based wireless sensor network using modified leach algorithm - Zeni, Saltihie (2012)
Wireless sensor networks (WSNs) composed from a large number of sensor node with the ability to sense and process data in the physical world in a timely manner. The sensor nodes contain a battery constraint which limit the network lifetime. Due to energy constraints, the deployment of WSNs will required advance techniques to maintain the network lifetime. A clustering based routing algorithm called Low- Energy Adaptive Clustering Hierarchy (LEACH) was proposed as a solution for low power consumption. This document is a study about LEACH algorithm where the implementation was done using OMNeT++ network simulator to study the performance of this algorithm in term of network lifetime. OMNeT++ was selected as a simulator because it provides some important features for this project like very good scalability unlike other simulators do. During this study, LEACH algorithm shows some drawbacks that need an improvements to overcome it as to improve the performance. Then, the modified LEACH algorithm was proposed where the improvement was done in cluster head selection based on LEACH. In cluster head selection, modified LEACH taking into account the residual energy of each node for calculation of the threshold value for next round. Meanwhile in LEACH, the cluster head selection was based on distributed algorithm. Both of these protocols was implemented in network simulator to compare the performance. This study shows that there were a better performance achieved by modified LEACH depends on the results obtained.